Disease Burden, Risk Factors, and Trends of Leukaemia: A Global Analysis - Huang, Junjie; Chan, Sze Chai; Ngai, Chun Ho; Lok, Veeleah; Zhang, Lin; Lucero-Prisno, Don Eliseo; Xu, Wanghong; Zheng, Zhi-Jie; Elcarte, Edmar; Withers, Mellissa; Wong, Martin C. S. (Frontiers in Oncology, 2022)
Leukaemia accounted for approximately 2.5% of all new cancer incidence and 3.1% of cancer-related mortality. The investigation of its risk factors and epidemiologic trends could help describe the geographical distribution and identify high-risk population groups. This study aimed to evaluate the global incidence, mortality, associated risk factors, and temporal trends of leukaemia by sex, age, and country. We extracted incidence and mortality of leukaemia from GLOBOCAN, CI5, WHO mortality database, NORDCAN, and SEER. We searched the WHO Global Health Observatory data repository for the age-standardised prevalence of lifestyle and metabolic risk factors. We tested the trends by calculating Average Annual Percentage Change (AAPC) from Joinpoint regression. The age-standardized rate of incidence and mortality were 5.4 and 3.3 per 100,000 globally. The incidence and mortality of leukaemia were associated with Human Development Index, Gross Domestics Products per capita, prevalence of smoking, physical activity, overweight, obesity, and hypercholesterolaemia at the country level. Overall, more countries were showing decreasing trends than increasing trends in incidence and mortality. However, an increasing trend of leukaemia incidence was found in Germany, Korea, Japan, Canada and the United Kingdom (AAPC, 2.32-0.98) while its mortality increased in the Philippines, Ecuador, Belarus, and Thailand (AAPC, 2.49-1.23). There was a decreasing trend of leukaemia for the past decade while an increase in incidence and mortality was observed in some populations. More intensive lifestyle modifications should be implemented to control the increasing trends of leukaemia in regions with these trends. Future studies may explore the reasons behind these epidemiological transitions.